2013
DOI: 10.1002/xrs.2519
|View full text |Cite
|
Sign up to set email alerts
|

Choice of optimal conditions for X‐ray fluorescence analysis of milk products with varying fat content

Abstract: The design of experiments was used to study sources of errors in the sample preparation and to choose optimal conditions for X‐ray fluorescence (XRF) analysis of milk products of varying fat content. The measurements were performed using the conventional wavelength‐dispersive XRF (WDXRF) and the total reflection XRF (TXRF) techniques. For WDXRF, the dried milk samples were pelletized, and the mathematical models were constructed, which described the dependence of XRF intensity on the pelletizing pressure, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…ences between cheese types did not affect the ability of the XRF to successfully determine Na. These findings are similar to other studies looking at the effect of fat content in milk powders on the determination of several minerals using XRF (Gunicheva, 2010;Smagunova and Pashkova, 2013). Based on this result, any natural cheese type (regardless of gross composition) can be successfully analyzed using any of the 6 calibration methods created with an individual cheese type.…”
Section: Effect Of Cheese Form Thickness and Composition On Na Peaksupporting
confidence: 87%
See 3 more Smart Citations
“…ences between cheese types did not affect the ability of the XRF to successfully determine Na. These findings are similar to other studies looking at the effect of fat content in milk powders on the determination of several minerals using XRF (Gunicheva, 2010;Smagunova and Pashkova, 2013). Based on this result, any natural cheese type (regardless of gross composition) can be successfully analyzed using any of the 6 calibration methods created with an individual cheese type.…”
Section: Effect Of Cheese Form Thickness and Composition On Na Peaksupporting
confidence: 87%
“…A layer of oil (oiling off) was observed on the sample film after the final reading and Na intensity decreased with increasing residence time in the autosampler (results not shown). Similarly, Smagunova and Pashkova (2013) found discoloration in both skim and whole milk powder-pellets and oiling off in whole milk powder-pellets after successive measurements and long measurement times (>20 min per sample; sample chamber temperature was ~38°C). Smagunova and Pashkova (2013) reported that the melting of fat contributes to scattering (enhancement of the XRF intensity) effects when measuring elements like Na due to primary and secondary radiation.…”
Section: Xrf Operating Parameters: Effect Of Current Voltage and Rumentioning
confidence: 93%
See 2 more Smart Citations
“…T-XRF can be successfully applied as a screening tool for chemical composition and quality control in the analysis of milk. Smagunova and Pashkova (2013) provided recommendations in sample pre-treatment of liquid milk with different fat contents (1.5-4.0%) for the analysis of minerals by T-XRF. The authors recorded an increase in the repeatability of calcium outcomes, when milk was diluted with water (to 5% total solid content) prior to the lyophilization step.…”
Section: Instrumental Neutron Activation Analysismentioning
confidence: 99%